2019
DOI: 10.1039/c8ra10366f
|View full text |Cite
|
Sign up to set email alerts
|

Comparative research on three types of MIL-101(Cr)-SO3H for esterification of cyclohexene with formic acid

Abstract: MIL-101(Cr)-SO3H was prepared with three different mineralizers, namely HCl, HF and NaAC, respectively. And catalytic performance and stability of three samples catalyzing the esterification of cyclohexene with formic acid were compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…The diffraction peaks corresponding to reflection planes are indexed, and the obtained samples exhibited strong diffraction peaks at 2θ 5.50 0 , 8.55 0 , and 9.90 0 , which correspond to the crystal‐plane diffraction of 311, 531, and 606, which are typical diffraction peaks for MIL‐101(Cr) and indicating that the synthesized material has the MIL‐101(Cr) phase having good crystallinity. [ 72 ] The results also show the crystalline structures of MIL‐101(Cr), MIL‐101(Cr)‐NH 2 , and MIL‐101(Cr)‐SO 3 H, and it can be seen that they have incredibly similar diffraction patterns. The ligand used in NH 2 ‐MIL‐101(Cr) was 2‐aminoterephthalic acid (H 2 BDC‐NH 2 ), which is structurally identical to the 1,4‐benzenedicarboxylate (BDC) ligand used in MIL‐101(Cr), and hence, it can be concluded that they have the same crystal structure.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The diffraction peaks corresponding to reflection planes are indexed, and the obtained samples exhibited strong diffraction peaks at 2θ 5.50 0 , 8.55 0 , and 9.90 0 , which correspond to the crystal‐plane diffraction of 311, 531, and 606, which are typical diffraction peaks for MIL‐101(Cr) and indicating that the synthesized material has the MIL‐101(Cr) phase having good crystallinity. [ 72 ] The results also show the crystalline structures of MIL‐101(Cr), MIL‐101(Cr)‐NH 2 , and MIL‐101(Cr)‐SO 3 H, and it can be seen that they have incredibly similar diffraction patterns. The ligand used in NH 2 ‐MIL‐101(Cr) was 2‐aminoterephthalic acid (H 2 BDC‐NH 2 ), which is structurally identical to the 1,4‐benzenedicarboxylate (BDC) ligand used in MIL‐101(Cr), and hence, it can be concluded that they have the same crystal structure.…”
Section: Resultsmentioning
confidence: 88%
“…Hence, the FTIR spectrum confirms the successful grafting of the −SO 3 H functional group on the MIL‐101(Cr) framework. [ 72 ] Figure 5 demonstrates the characteristic peak of the amine stretching vibration, which appeared at 3490 and 3378 cm −1 for MIL‐101‐NH 2 . Another characteristic peak was observed for the asymmetric for C–N bonds at 1360–1290 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, thermal treatment of these materials directly influences their acidity and consequently their catalytic activity, since at high temperatures hydrated niobium oxide loses its surface hydroxyl groups, and thus its Brønsted acidity is reduced 20. However, several studies have been carried out aiming at modification of the catalyst surface by the insertion of acid functional groups such as sulfonic acids (–SO 3 H) or organic acids to increase the catalyst efficiency for several applications 7, 21, 22.…”
Section: Introductionmentioning
confidence: 99%